BEHAVIOR OF RESPIRATORY MUSCLE STRENGTH AND HANDGRIP DURING A HEMODIALYSIS SESSION (Interdisciplinary Studies Journal, 2026)
Chronic kidney disease (CKD) leads to a loss of water-electrolyte balance and a reduction in muscle strength due to uremic syndrome. The aim of this study was to assess the respiratory and peripheral muscle strength of patients undergoing dialysis. This was an observational, cross-sectional, quantitative and descriptive study of 40 patients undergoing treatment in a renal therapy unit in a municipality in the northwest of the state of Rio Grande do Sul. A manovacuometer was used to assess respiratory muscle strength and a dynamometer was used to assess handgrip strength before dialysis and every hour during the treatment session, before hemodialysis (HD), after 1h, 2h, 3h and 4h of treatment. The results obtained were described using the mean, percentage and standard deviation. The significance level adopted was 5% (p0.001). Finally, with regard to handgrip strength, there was a decrease between the pre-HD assessment (27.43 ± 8.51) and the last one (25.53 ± 8.75), both with p>0.001. At the end of the study, it was clear that patients with CKD undergoing HD showed a reduction in expiratory and peripheral muscle strength over the hours of treatment.
Keywords: Chronic kidney disease; Dynamometry; Manovacuometry